Development and validation of a National Prostalgia scale to measure acceptance and desire for cultural change - Corral, Sol I.; Bray, Jessica R.; Jones, Daniel N.; Armenta, Angel D.; Zárate, Michael A. (Frontiers in Social Psychology, 2024)
Demographic changes occurring throughout the world, as well as different forms of climate and social movements, are examples of the constant cultural change people experience. Many of these changes reflect broad political and existential threats. We developed and tested the concept of national prostalgia, which we define as the longing of the nation's future. According to Cultural Inertia theory, national prostalgia is a psychological propeller that facilitates acceptance of cultural change. We conducted two correlational studies to develop and test the construct, and the predictive, divergent, and convergent validity of national prostalgia by comparing it to two prospection scales that measure future-thinking, and a third study to experimentally test if national prostalgia can be manipulated. We hypothesized that national prostalgia would predict higher acceptance to cultural change. Change was operationalized as eco-friendly intentions, engagement of new norms created during the COVID-19 pandemic and lowering prejudiced attitudes-beyond the effect of national nostalgia, prospection, optimism, and openness to new experiences. Study 1 demonstrated that national prostalgia was a better predictor than prospection for higher eco-friendly intentions and acceptance of new normal norms, even when controlling for national nostalgia (i.e., a psychological anchor). In study 2, national prostalgia predicted higher eco-friendly intentions and acceptance of new normal norms, even when controlling for prospection, optimism, and openness to new experiences. National prostalgia did not predict outgroup derogation or white nationalism-variables that indicate prejudice. Study 3 replicated the basic effects, but manipulations designed to influence national prostalgia did not have their predicted effects. Thus, national prostalgia is a psychological propeller that goes above and beyond the effect of prospection and we now have a reliable and valid scale to measure national prostalgia.